Intraspecific polymorphism in mystus nemurus (C&V) detected by RAPD-PCR fingerprinting - Leesanga, Sanga; Siraj, Siti Shapor; Daud, Siti Khalijah; Harmin, Sharr Azni (Universiti Putra Malaysia Press, 2004)
Yellow catfish, Mystus nemurus (C&V), is becoming one of the majorfreshwater species farmed l7y aquaculturists in Southeast Asia. It was of interest to examine levels of genetic sub-population differentiation among samples of this species obtained from parts of its range, as well as to compare the genetics of wild and hatchery-bred fish. The genetic aspects of variation in the fish, which were collected from eight wild populations throughout Thailand and a hatchery stock, were determined at molecular (DNA) level using the technique ofRAPD-PCRfingerprinting. Five arbitrary primers namely OPA-11, OPA-14, OPA-18, OPA-19 and OPA-20 were chosen to amplify products, which showed 28 polymorphic loci in 9 populations. The highest genetic distance (D) was found between Chainat and Suratthani populations with the value of 0.289, while the lowest was found in Songkhla population and hatchery stock with the value of 0.087. The dendrogram depicts the genetic relationship among populations of M. nemurus, which are grouped into four clusters according to their regional areas.